Advances in the Ecohydrology of Arid Lands (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This is a Special Issue (SI) of Hydrology. The title of the SI is “Advances in the Ecohydrology of Arid Lands”. Ecohydrology is an emerging, cross disciplinary subfield of hydrology devoted to the mutual interactions between water and ecosystems. Today, the important question of what these interactions mean for human society and how human society impacts these interactions is also part of this subject. The specific climatic/geographic focus here is on arid lands broadly defined as water-deficient regions where potential evapotranspiration (PET) exceeds precipitation (P). The intent of the SI is to present scientifically accurate information on the current state of leading ecohydrology oriented research on arid lands, representing the best contemporary thinking in the field. The five research articles presented by no means cover the field but provide an introduction to the variety of current research. The intended audience is not only those involved in this field but also those engaged in the more traditional aspects of hydrology, biology, ecology, geography, engineering, water management, agriculture urban planning, and other relevant fields.